2021
DOI: 10.1111/jpn.13569
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of amino acids and minerals to the egg yolk and to the yolk sac of their progeny is affected by breeder age

Abstract: This study aimed to assess the effects of breeder age on egg quality and amino acid and mineral transfer to the egg yolk and yolk sac of newly hatched chicks. Three ages (32, 42 and 52 weeks) of the same commercial flock of Hubbard breeders were studied. A total of 465 eggs were used for each age, with 60 being used for determining egg quality and amino acid and mineral content of yolk, and 405 for incubation period to obtain and evaluate the yolk sac of chicks. Breeders aged 52 weeks had heavier eggs and a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Older breeders had greater egg weight and yolk weight ( p ≤ 0.05) than young breeders (Table 2). These results were expected, as egg size is known to be positively related to breeder age, with egg size increasing as breeder's age (Araújo et al, 2016; Iqbal et al, 2017; Santos et al, 2021). The main reason for the increase in egg size is the increase in yolk size (Nangsuay et al, 2013).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Older breeders had greater egg weight and yolk weight ( p ≤ 0.05) than young breeders (Table 2). These results were expected, as egg size is known to be positively related to breeder age, with egg size increasing as breeder's age (Araújo et al, 2016; Iqbal et al, 2017; Santos et al, 2021). The main reason for the increase in egg size is the increase in yolk size (Nangsuay et al, 2013).…”
Section: Resultsmentioning
confidence: 73%
“…Young breeders have a greater capacity for depositing protein and amino acids in the yolk of fertile eggs. Embryos of older breeders, however, seem to use the nutrients present in the yolk more efficiently during embryonic development (Santos et al, 2021). Despite this difference between the transfer of amino acids and use, the consumption of immunoglobulin seems to be the same, regardless of the breeder age.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the enhanced Ca concentration in the second half of incubation, it can be concluded that Ca deposits from the eggshell into the yolk are higher than Ca uptake by the embryonic circulatory system during this period. Some authors evaluated the effect of breeder birds' age on the mineral content of egg yolk (32). It was shown that transfer of P, K, Ca, Mg, Cu, Fe, Mn and Zn from breeder hens to egg yolks was affected by breeder age, and the content of the previously stated minerals in egg yolks from 32-week-old birds was higher than that of older birds (42 and 52 weeks old) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors evaluated the effect of breeder birds' age on the mineral content of egg yolk (32). It was shown that transfer of P, K, Ca, Mg, Cu, Fe, Mn and Zn from breeder hens to egg yolks was affected by breeder age, and the content of the previously stated minerals in egg yolks from 32-week-old birds was higher than that of older birds (42 and 52 weeks old) [32]. The egg yolks of young breeders (28 weeks old) contained more minerals than those of older breeders (34 and 40 weeks old) in ducks [33].…”
Section: Discussionmentioning
confidence: 99%